Polysaccharide Biosynthesis: Glycosyltransferases and Their Complexes - Zabotina, Olga A.; Zhang, Ning; Weerts, Richard (Frontiers in Plant Science, 2021)
Glycosyltransferases (GTs) are enzymes that catalyze reactions attaching an activated sugar to an acceptor substrate, which may be a polysaccharide, peptide, lipid or small molecule. In the past decade, notable progress has been made in revealing and cloning genes encoding polysaccharide synthesizing GTs. However, the vast majority of GTs remain structurally and functionally uncharacterized. The mechanism by which they are organized in the Golgi membrane, where they synthesize complex highly-branched polysaccharide structures with high efficiency and fidelity, is also mostly unknown. This review will focus on current knowledge about plant polysaccharide synthesizing GTs, specifically focusing on protein-protein interactions and the formation of multiprotein complexes.